Prevalencia de helicobacter pylori en pacientes con gingivitis y enfermedad peridontal - Moroni Nakata, Hilda (2001)
With the objetive of detennine the helicobacter pylori (Hp) prevsalencv in patiens with gingivitis and periodontal disease, it was collected and processed sullgingival plate samples from 177 patients whose have been classffied according to: 1) Ulcer and gingivitis, 2) gastritis and gingivitis, 3) gingivitis and 4) periodontitis aleatoriamente selected at the Odontological Clinic! of San Marcos University It was recovered Hp in 9,4%ftom the studied poblation, tnoreftecuenilly in women (6,8%) than in men (2,6 %). Helicobacerpylori was recovered.front the 7,7 % qfpatients with giligivitis, and from the 1,7% of patients with gastritis and gingivitis. Principally Hp was recovered neither from patients with ulcer and gingivitis nor patienty with periodontitis. principally Hp was recovered form people between 20 and 30 years old, and more frecuently in womwn than in men.